PEMANFAATAN LEMBAR KERJA MAHASISWA UNTUK MENINGKATKAN KEAKTIFAN MAHASISWA: STUDI PENERAPAN LESSON STUDY PADA MATA KULIAH BUKU TEKS PELAJARAN BAHASA INDONESIA - Febriani, Meina (Jurnal Pendidikan Bahasa dan Sastra, 2016)
AbstractThis study emphasizes that choice and use of an appropriate teaching material may support the students’ participation during the lecturing process. Students’ worksheet as one of printed teaching material is considered to be able to enhance students’ participation. Specifically, this study presents: (1) the forms and characteristics of students’ worksheet that may support students’ participation; (2) the increase of students’ participation in learning through the students’ worksheet implementation. This study belongs to descriptive study towards the results of controlled observation, while treatments applied during the lesson study comprise four cycle of stages with the implementation of plan, do, and see stages in each cycle. Data in this study is obtained from study document and observation during the lecture of Bahasa Indonesia Text Book Course in 2016. Results show several empirical discoveries. First, the students’ worksheet has a special format that is relevant with the substance of material as well as supported by its appropriate use. Second, statistically, the use of students’ worksheet can enhance students’ participation up to 71%, 79%, 86%, and 89% from cycle I to IV, respectively.Keywords: text book, participation, lesson study, worksheet, learning